THE EFFECT OF COMIC STRIPS ON SECONDARY EFL STUDENTS’ READING COMPREHENSION AND WRITING ABILITY - M. Ridhwan; Muhammad Taufik Ihsan; Naskah Naskah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The purpose of this study was to investigate the significant effect of using comic strips strategy toward students’ reading comprehension and writing ability at MTsN 1 Pekanbaru. A Quasi-Experimental by Non-equivalent Pre-test and Post-test Group was applied as a designed for study. The sample was two classes (VIII 3 and VIII 4) consisting 20 students of treatment class, and 20 students of control class. The data were computed using SPPS 20.0 to analyze Independent sample t-test and Paired sample t-test. The finding of this study revealed that there was a significant effect on students’ reading comprehension by using comic strips strategy, it shown on paired sample t-test; treatment class was 77 and control class was 64.5, the hypothesis testing showed the result of post T-test -7.149, then score of sig.(2-tailed) is 0.000, if we act to null hypothesis (Ho) that is 0.05, it means that the score of sig.(2-tailed) was smaller than score of Ho. The data also revealed that there was a significant effect on students’ writing ability, it shown on paired sample t-test; treatment class was 79.6 and control class was 54.2, the hypothesis testing showed the result of post T-test -21.9, then score of sig.(2-tailed) is 0.000, if we act to null hypothesis (Ho) that is 0.05, it means that the score of sig.(2-tailed) was smaller than score of Ho. Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. From those data it can be summarized that there is a significant effect of using comic strips strategy on students’ reading comprehension and writing ability.